Qualitative analysis of solutions of parabolic type equations with nonlocal boundary conditions - Novickij, Jurij; Ivanauskas, Feliksas (Lietuvos matematikos rinkinys, 2010)
The aim of the work is qualitative analysis of solutions of parabolic equations, non–negativity of solutions, investigation and modelling of physical parameters. All tasks were modelled using numerical analysis methods. Differential equations were solved using implicit finite difference method. Derived results could be used solving one–dimensional tasks with parabolic type equations in physics, biochemistry, chemistry and other sciences.